Water quality and shellfish related gastrointestinal disease cases in Kota Bharu, Kelantan, Malaysia - Aweng Eh Rak; Maketab Mohamed (2011)
The sampling of river water and shellfish was conducted three times between 26 February and 20 March 2006 at Sungai Ketereh, Kota Bharu Kelantan. Three sampling stations were identified for water quality and shellfish sampling. The objective of this study is to determine the correlation between water quality, shellfish tissue contaminations and the cases of gastrointestinal diseases in Kota Bharu. There are two stages of shellfish sampling, the first stage was raw "etak" from the riverbed and the second stage was processed "etak". Shellfish was sent to the bacteriology laboratory of the Fisheries Research Institute located in Batu Maung, Penang and water quality analysis was performed by an accredited laboratory.Meanwhile, data on the gastrointestinal disease cases was obtained from the Department of Health , Kota Bharu.The results have shown that, fecal coliform concentrations in the river water recorded was between 214.20-721.50 MPN/100ml (up-stream), 249.50-791.50 MPN/100ml(middle section) and 277.80-574.80 MPN/100ml (down-stream). On the other hand, the bacterial contamination in raw C. fluminea or "etak" was found to be higher and the concentration recorded was between 2,450-75,000 MPN/100g(up-stream), 1,550-151,500 MPN/100g(middle section) and 1,200-49,000 MPN/100g(down-stream). This was believed due to the filter feeding habit of the shellfish where the pollutants get accumulated in the tissues. The fecal coliform concentrations in processed "etak" tissues was also high in some batches while absent in some of them,and this was believed to be due to be the period of smoking process. The longer the smoke the more effective is the elimination of bacteria.Nine (9) samples were analyzed, four(4) of them contaminated with bacteria. The number of bacteria detected in the processed "etak" ranged from 325 MPN/100g to 5,125 MPN/100g. The data obtained on the incidence of gastrointestinal disease from 1998 to 2004 in Kota Bharu district showed that acute gastroenteritis was the highest number of cases recorded ranging from 2500 to 4000 cases per year and this was believed to be due to the consumption of "etak". The results revealed a positive correlation between river quality, shellfish and incidence of gastrointestinal disease in Kota Bharu